Energy management of PEM fuel cell/ supercapacitor hybrid power sources for an electric vehicle. (17th August 2017) - Allaoua, Boumediene; Asnoune, Khadidja; Mebarki, Brahim
Abstract: This paper presents the utilization of a supercapacitor (SC) as an auxiliary power source in an electric vehicle (EV), composed of a proton electrolyte membrane fuel cell (PEMFC) as the main energy source. The main weak point of PEMFC is slow dynamics because one must limit the fuel cell current slope in order to prevent fuel starvation problems, to improve its performance and lifetime. The very fast power response and high specific power of a supercapacitor can complement the slower power output of the main source to produce the compatibility and performance characteristics needed in a propulsion system. DC-DC converters connected to the hybrid source ensure a constant voltage value in inverters inputs. After an architecture presentation of the hybrid energy source, two parallel-type configurations are explored in more detail. For each of them, the energy flow control and management, validated simulation shows the performance obtained in this configuration. The hybrid source management is based primarily on the intervention of the supercapacitor in fugitives' schemes such as slopes, different speeds and rapid acceleration. Secondly, the PEMFC intervenes to guarantee the power in permanent regime. Finally, simulation results considering energy management are presented and illustrated the hybrid energy source benefits. Graphical abstract: Real electric vehicle with hybrid energy source. Highlights: A supercapacitor association is proposed for electric vehicle applications to solve the main weak point of PEMFC. Performances of the DC/DC converters are planned for the energy flow control and management in the EV propulsion system. A hybrid energy source simulation approach to surge the accurate modeling is presented. Study permits the prediction of hybrid source behavior under different scenarios.